Islamism and Social Reform in Kerala, South India - FILIPPO OSELLA and CAROLINE OSELLA (Modern Asian Studies 42, 2/3 (2008), 2008)
This paper critiques ethnographic tendencies to idealise and celebrate sufi 'traditionalism' as authentically SouthAsian.Weperceive strong academic trends of frank distaste for reformism, which is then inaccurately-and dangerously buttressing Hindutva rhetoric-branded as going against the grain of South Asian society.This often goes along with (inaccurate) branding of all reformism as `foreign inspired' or wah'habi. Kerala's Mujahids (Kerala Naduvathul Mujahideen [KNM]) are clearly part of universalistic trends and shared Islamic impulses towards purification. We acknowledge the importance to KNM of longstanding links to the Arab world, contemporary links to the Gulf, wider currents of Islamic reform (both global and Indian), while also showing how reformism has been producing itself locally since the mid-19th century. Reformist enthusiasm is part of Kerala-wide patterns discernable across all religious communities: 1920s and 1930s agitations for a break from the 19th century past; 1950s post-independence social activism; post 1980s religious revivalism. Kerala's Muslims (like Kerala Hindus and Christians) associate religious reformism with: a self-consciously`modern' outlook; the promotion of education; rallying of support from the middle classes. There is a concomitant contemporary association of orthoprax traditionalism with `backward', superstitious and un-modern practices, troped as being located in rural and low-status locations